Inter‐harmonics monitoring method based on PMUs. Issue 18 (11th August 2017) - Liu, Hao; Bi, Tianshu; Li, Jue; Xu, Sudi; Yang, Qixun
Abstract : More and more inter‐harmonics are brought to the power grid due to the integration of renewables and the wide‐area deployments of the electronic devices. This may lead to the exacerbation power system stability problems such as the subsynchronous oscillation in western China. The synchronisation and high‐reporting rates of phasor measurement units (PMUs) make them an effective tool to monitor the appearance, propagation and distribution of inter‐harmonics for protection and control strategies. In this study, the instantaneous powers of the single phase and the three phase that contain inter‐harmonics are analysed. The phasor value of the signal containing the inter‐harmonics is computed. It is found that the analysis based on the instantaneous power, phasor magnitude or phasor angle cannot distinguish whether the harmonic is subsynchronous or supersynchronous. Then, an inter‐harmonics monitoring method that is based on complex numbers of phasor measured by PMUs is proposed in this study. This proposed method has been implemented in the main station of the wide‐area measurement system in western China. A number of field data events are used to verify the correctness of the theoretical derivations.